Analisis Yuridis Perlindungan Hukum Terkait Jumlah Jam Kerja Bagi Remote Workers Di Indonesia - Intan Azzahra Nur Salsabila; Raudha Maghfirolaita Wahyudi; Ayunita Rohanawati; Mukmin Zakie (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The aim of this research is to discuss the protection of the rights of remote workers in Indonesia. Legal protection for remote workers includes work agreements, wages, leave, working hours, protection regarding the right to wages, obtaining social security for employment, the right to occupational safety and health, and the right to organize or associate. There are two issues raised in this research, namely what regulations relate to worker protection for remote workers and what forms of protection relate to the number of working hours for remote workers. The research method chosen is juridical-normative legal research which uses a statutory approach and a comparative approach. The data used is secondary data by collecting primary legal materials and secondary legal materials. The results of this research show that there are still no regulations governing remote work so that legal protection for remote workers cannot be met.